Health Matters - Jhingan, Shikha (India, 2006)
The film takes a panoramic look at health care in India through the everyday experiences of patients in both public and private hospitals, covering a range of rural and urban locations.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films